Hydrophobic adsorption in ionic medium improves the catalytic properties of lipases applied in the triacylglycerol hydrolysis by synergism - Quilles Junior, José Carlos [UNESP]; Ferrarezi, Ana Lúcia [UNESP]; Borges, Janaina Pires [UNESP]; Brito, Rafaela Rodrigues [UNESP]; Gomes, Eleni [UNESP]; da Silva, Roberto [UNESP]; Guisán, José Manuel; Boscolo, MaurÃcio [UNESP] (Springer Nature, 2016)
It is known that lipases may have their catalytic properties improved by the action of some salts or by the adsorption on hydrophobic supports. However, what we present in this work is more than that: we evaluate the combination of these two factors of hyperactivation of lipases from Acremonium-like ROG 2.1.9, a study that has not been done so far. This work proves that a synergistic effect occurs when the lipases are immobilized on hydrophobic supports at the presence of sodium chloride and are applied in triacylglycerol hydrolysis. This assay made it possible to achieve the highest hyperactivation of 500 % with the lipases immobilized on Phenyl-Sepharose and applied with 0.1 M of sodium chloride. Besides this positive effect on enzyme activity, the use of these two factors led to the thermal stability increasing of the immobilized lipases. For this derivative, the recovered activity was approximately 85 % after 6 h incubated at 55 °C and 1.0 M of the sodium chloride against 50 % of the same derivative without this salt. Furthermore, others assays were performed to prove the evidences about the synergistic effect, showing a promising method to improve the catalytic properties of the lipases from Acremonium-like ROG 2.1.9.
Keywords: Hydrolysis; Hyperactivation; Immobilization; Lipases; Synergism